2017
DOI: 10.3141/2616-01
|View full text |Cite
|
Sign up to set email alerts
|

Operating Speed on a Buffer-Separated Managed Lane

Abstract: Managed lanes typically are on or adjacent to freeways and are actively operated and managed to preserve operational performance—such as more optimal travel speeds—over comparable general-purpose traffic lanes. A study was conducted to evaluate speeds on existing buffer-separated managed lanes to identify variables that influence operating speed. Speed data from more than 130 unique sites in Los Angeles, California; Orange County, California; and Dallas, Texas, were used. All analyses showed that the managed l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…In Part I of this paper series (Wright et al, 2019), we proposed several macroscopic modeling elements for the purpose of mathematically describing a freeway equipped with a managed lane facility (a "managed lane-freeway network"). Part I discusses the road-topological considerations of modeling two parallel traffic flows, as well as mathematical descriptions for several of the complex emergent (and sometimes counteracting) phenomena that have been observed on managed lane-freeway networks, like the so-called friction (Liu et al, 2011;Fitzpatrick et al, 2017) and smoothing (Menendez and Daganzo, 2007;Cassidy et al, 2010;Jang and Cassidy, 2012) effects.…”
Section: Introductionmentioning
confidence: 99%
“…In Part I of this paper series (Wright et al, 2019), we proposed several macroscopic modeling elements for the purpose of mathematically describing a freeway equipped with a managed lane facility (a "managed lane-freeway network"). Part I discusses the road-topological considerations of modeling two parallel traffic flows, as well as mathematical descriptions for several of the complex emergent (and sometimes counteracting) phenomena that have been observed on managed lane-freeway networks, like the so-called friction (Liu et al, 2011;Fitzpatrick et al, 2017) and smoothing (Menendez and Daganzo, 2007;Cassidy et al, 2010;Jang and Cassidy, 2012) effects.…”
Section: Introductionmentioning
confidence: 99%
“…Buffer separation and other geometric strategies can help to preserve these benefits. Recent research has found that higher speeds are associated with wider buffers ( 2 ). The wider ML buffer separation, travel lane, or shoulder width may also positively influence safety.…”
mentioning
confidence: 99%